Pengaruh Kualitas Sumber Daya Manusia Terhadap Produktivitas Perusahaan Pada PT. Duta Intra Yasa Yogyakarta - Henny Henny (Jurnal Manajemen dan Ekonomi Kreatif, 2024)
The quality of human resources greatly affects the productivity of the company because the company needs a competent workforce in its field so that the company's goals can be achieved. The company PT. Duta Intra Yasa is a distribution company or product consumer company that distributes PT. Deltomed (Antangin) and PT. Ultrasakti (Freshcare). Because it is based on a distribution company with a method of equitable distribution of products in the market, KPI (Key Performance Indicator) is needed as a tool to measure human resource productivity at PT. Ambassador Intra Yasa. This study uses an interview method with Regional Sales Managers from PT. Ambassador Intra Yasa to find out the influence of KPI transparency on human resource productivity. And the results of this study show that all teams in the company. PT. Duta Intra Yasa knows and understands the targets in his work so that it can be a reference to assess his work productivity.